Período da polinização à formação da chamada preta em grãos de milho: Herança e correlação genética com alguns caracteres agronômicos - Alves Soares, Antônio; Domingos Galvão, José; Silva, José Carlos (Revista Ceres, 2025)
In a work carried out at the Federal University of Viçosa, Minas Gerais, Brazil, the inheritance of the grain filling period in corn and the correlations among the length of this period with yield of grains and other related characters were studied.